Transoceanic migration network of dragonfly Pantala flavescens: origin, dispersal and timing - Ranjan, Kumar Sanat; Pawar, Amit A.; Roy, Arnab; Saha, Sandeep (Frontiers in Ecology and Evolution, 2023)
The awe-inspiring multi-generational, transoceanic migration circuit of dragonfly species, Pantala flavescens stretches from India to Africa. Understanding the collective role of wind, precipitation, fuel, breeding, and life cycle driving the migration remains elusive. We identify the transoceanic migration route from years 2002 to 2007 by imposing an energetics-based time-constraint on a modified Dijkstra’s path-planning algorithm incorporating active wind compensation. The prevailing winds play a pivotal role; the Somali Jet enables migration across the Indian Ocean from Africa to India, whereas the return requires stopovers at the disappearing islands of the Maldives and Seychelles. The migration timing, identified using monthly-successful trajectories, life cycle, and precipitation data, corroborates sightings. A branched-network hypothesis connects our sighting in Cherrapunji (North-East India), the likely origin, to the known migration circuit.